Evaluation of a New Brain Tissue Probe for Cerebral Blood Flow Monitoring in an Experimental Pig Model. Issue 6 (9th September 2016) - Seule, Martin; Isaak, Rimmon; Sanchez-Porras, Renan; Sakowitz, Oliver; Keller, Emanuela; Unterberg, Andreas; Orakcioglu, Berk
Abstract: BACKGROUND: Bedside monitoring of cerebral blood flow (CBF) may provide new insights into the pathophysiology of brain injury, allow early detection of secondary ischemia, and help guide therapy. OBJECTIVE: To evaluate a new brain tissue probe for serial CBF monitoring using near-infrared spectroscopy and indocyanine green dye dilution (NeMo Probe) compared with the existing thermal diffusion probe (QFlow 500 Probe). METHODS: In 7 pigs, the NeMo Probe and QFlow 500 Probe were inserted into the subcortical white matter. Parallel measurements were recorded during (1) baseline, (2) hypotension, (3) hypertension, and (4) hyperventilation. Thereafter, protocol points 1 through 4 were repeated once. The Spearman correlation ( r s ), Bland-Altman plot, concordance rate, and coefficient of variation were used for statistical analysis. RESULTS: There was poor agreement between 56 pairs of absolute CBF values ( r s = 0.52, P < .001). The mean bias was 10.7 mL·100 g −1 ·min −1 with limits of agreement of −33.0 to 54.3 mL·100 g −1 ·min −1 . The analysis of 49 pairs of changes in CBF showed a good correlation ( r s = 0.83, P < .001), and the concordance rate was 93.3%. The coefficient of variation from repeated measurements under comparable physiological conditions was 51.6% for the QFlow 500 Probe and 12.9% for the NeMo Probe. CONCLUSION: Absolute CBF values obtained with the NeMo Probe and QFlow 500 Probe cannot be interpreted as equivalent. However, the NeMo Probe provides acceptable trending ability and reproducibility from repeated measurements, whereas the reproducibility of the QFlow 500 Probe was poor. Future clinical studies are warranted to evaluate the NeMo Probe in the setting of acute brain injury.